Formal synthesis of valiolamine from myo-inositol - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (Tetrahedron, 2011)
An efficient formal synthesis of racemic valiolamine starting from readily available myo-inositol is reported. In all the synthetic steps only one regioisomer is formed, which circumvents laborious purification of products. Regioselective benzylation of myo-inositol orthoformate, super-hydride mediated deoxygenation of a cyclitol derivative and stereoselective addition of dichloromethyllithium to an inosose are the key reactions in the synthesis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Amino sugar; Carbohydrate; Cyclitol; Inositol; Natural product; Valiolamine